The effect of web-based professional development study to mathematics teachers' problem solving strategies - ÖZDEMİR, AHMET ŞÜKRÜ; PUSMAZ, ALAATTİN (ELSEVIER SCIENCE BV, 2012)
This research analyzes the problem-solving strategies adopted by math teachers in middle school and explores the role of web-based professional development studies in improving this process. The case group is constituted by twelve math teachers teaching in middle school. These twelve teachers have been arranged a seven-week web-based professional development study in problem-solving strategies. In collecting the data, pre- and post-testing, interview and observation methods have been exercised. On the basis of content analysis, the data obtained have been examined through an inductive strategy. (C) 2012 Published by Elsevier Ltd. Selection and/or peer review under responsibility of Prof. Dr. Huseyin Uzunboylu
Keywords: Problem solving; mathematics teachers; web based professional development